A Comparative Study on the Physicochemical Parameters of Camel and Buffalo Milk - Singh, Sajjan; Poonia, Rakesh Kumar; Singh, Raghvendar; Mehta, S.C.; Patil, N.V. (Journal of Buffalo Science, 2013)
This research work was carried out to compare the various physicochemical parameters of two species, camel and buffalo. Camel milk samples were collected at National Research Centre on Camel, Bikaner and buffaloes milk samples were collected from the surroundings villages of Bikaner. After collection milk samples were brought to the laboratory of NRCC Bikaner and they were analyzed for fat, SNF (Solid Not Fat), protein, lactose, total ash and pH using milk analyzer (Lactoscan). Camel milk had 2.71±0.11 fat, 6.91±0.03 SNF, 2.23±0.02 protein, 3.86±0.02 lactose, 0.79±0.004 total ash and 6.95±0.01 pH while buffalo milk had 8.71±0.82 fat, 8.44±0.19 SNF, 4.11±0.02 protein, 4.46±0.15 lactose, 0.98±0.05 total ash and 7.59±0.02 pH. Fat, SNF, protein and pH of buffalo milk was significantly (P<0.001) higher than camel milk. Lactose and total ash in buffalo milk was also higher than camel milk but at P<0.05 level. So it can be concluded that all the studied parameters were high in buffalo milk than camel milk